SANITASI PEMUKIMAN PADA MASYARAKAT DENGAN RIWAYAT PENYAKIT BERBASIS LINGKUNGAN - Ahyanti, Mei (Politeknik Kesehatan Tanjung Karang, 2020)
Environmental-based diseases (PBL) are a health problem and occur in almost all geographical regions in the world. Every year, environment-based diseases are always found and reported to spread evenly at every Puskesmas in Bandar Lampung City. Settlement sanitation is an important aspect directly related to health and society.